Beyond the Cost of Price Adjustment: Investments in Pricing Capital - Mark Zbaracki; Mark Bergen; Shantanu Dutta; Daniel Levy; Mark Ritson (Bar-Ilan University, Department of Economics, 2005)
The literature on costs of price adjustment has long argued that changing prices is a complex and costly process. In fact, some authors have suggested that we should think of firms' price-setting activities as “producing” prices, similar to the way firms use production processes to produce goods and services. In this paper we explore one natural extension of this view, that besides observing costs of price adjustment, we should also expect to see firm-level investments in capital expenditures into these “pricing” production processes. We coin the term “pricing capital” for these investments, and suggest that they can improve the efficiency of the “pricing production” activities by both reducing the costs of adjusting prices, and improving the effectiveness of price adjustments in future periods. Using two types of data sources, we find compelling evidence of the existence as well as the importance of pricing capital in firms. The existence of firm-level “pricing capital” has the potential of fundamentally altering the way we think about pricing and price adjustment in many areas of economics. It suggests looking toward the “pricing capital” to decipher the likely degree and causes of price rigidity and its variation across price setters, markets, and industries. Moreover, “pricing capital” introduces a new, higher-level, pricing decision made by individual firms. Decisions to invest in pricing capital compete with traditional capital investment decisions that have long been studied in economics, such as capital investments in plant, equipment, and R&D. Furthermore, since pricing capital is a choice variable, it implies that costs of price adjustment often used in models of price rigidity are endogenous. As such, pricing capital offers new insights into the micro-foundations of the costs of price adjustment. The most provocative implication of the new theory of pricing, however, is that the allocative efficiency of the price system itself may be determined endogenously by individual price setters who choose whether and how much to invest in pricing capital.
Keywords: E31; E12; D21; D4; L11; L16; L22; 330; Economic Cost of Price Adjustment; Menu Cost; Managerial and Customer Costs of Price Adjustment; Pricing Capital; Price Rigidity; Sticky Prices; Rigid Prices; Micro-foundations; Allocative Efficiency; Price System; Endogenous Price Adjustment Cost